2016
DOI: 10.2147/imcrj.s106396
|View full text |Cite
|
Sign up to set email alerts
|

Kikuchi-Fujimoto disease and systemic lupus erythematosus

Abstract: Kikuchi–Fujimoto disease, or histiocytic necrotizing lymphadenitis, is an infrequent idiopathic disorder. It has been associated with autoimmune disorders, of which systemic lupus erythematosus is the most outstanding. The basis of its diagnosis relies on the histological examination of lymph nodes, which typically reveals necrosis surrounded by histiocytes with crescentic nucleus, immunoblasts and plasma cells, and absence of neutrophils. We report the case of a 27-year-old Argentinian female patient without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 37 publications
0
60
0
1
Order By: Relevance
“…Baenas et al noted three patterns of presentation of association between KFD and SLE which are before the onset of SLE (30%), simultaneous occurrence of both disorders (47%), and KFD after SLE (23%) [16]. Goldblatt et al…”
Section: Discussionmentioning
confidence: 99%
“…Baenas et al noted three patterns of presentation of association between KFD and SLE which are before the onset of SLE (30%), simultaneous occurrence of both disorders (47%), and KFD after SLE (23%) [16]. Goldblatt et al…”
Section: Discussionmentioning
confidence: 99%
“…There are a lot of studies showing association between SLE and KFD, but the relationship is not clearly understood. 10,11,12 Histologically SLE differs from KFD in that it is associated with the presence of hematoxylin bodies, which are particles of denatured nuclear material. Londhey et al reported a case where a patient was initially diagnosed with KFD, but later went on to develop SLE, and suggested that it may precede, follow or coincide with the diagnosis of SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical lymphocytes may also be seen on a peripheral blood smear. 5 The origin of Kakuchi-Fujimoto Disease is unknown but a viral etiology has been hypothesized including Epstein-Barr virus, human herpes virus 6, rubella virus, parvovirus B19, varicella zoster, paromyxovirus and parainfluenza virus 4, 6 . There has been some postulation of possible genetic predisposition based on familial occurrence 6 , but this has not been clearly elucidated to date.…”
Section: Case Presentationmentioning
confidence: 99%
“…A review of 244 cases of Kakuchi-Fujimoto Disease in the literature by Kucukardali found 32 cases (13%) were associated with systemic lupus erythematosus 3 . A subsequent literature review described three patterns of presentation including KFD before the onset of SLE (30%), simultaneous occurrence of both disorders (47%) and KFD after SLE diagnosis (23%) 5 . Given this association, it is important to be aware of the possibility of these diagnoses occurring contemporaneously.…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation